Prevalência e determinação dos sorotipos circulantes de Streptococcus pneumoniae em crianças que frequentam creches no município de Goiânia-GO - Guerreiro, Tainá Carvalho (2015)
Streptococcus pneumoniae remains as a major cause of childhood morbidity and mortality worldwide, especially in developing countries. Nasopharyngeal colonization is the key of the development of pneumococcal diseases as well as for horizontal spread of this pathogen in the community. Children are the main reservoir of S. pneumoniae and act as vectors in the transmission chain of this microorganism. Pneumococcal conjugate vaccines protect against pneumococcal disease caused by vaccine serotypes, also contributes to the protection against colonization by the same serotypes. In 2010, PCV10 was introduced in the childhood immunization program of Brazil. This is a population-based study that was conducted immediately after the introduction of the vaccine in order to determine the carriage rate of this pathogen in children attending in day care centers in Goiania. These data may be used as a predictor for evaluating the dynamic of the circulating serotypes into the community after the vaccine introduction. Between October and November 2010, nasopharyngeal swabs were collected from 853 children ranging from 36 to 59 months attending in day care centers in Goiania. Isolation and identification of S. pneumoniae were done after the incubation step on broth-enriched for 6 h and posterior plating on blood agar. Isolates that were α-haemolytic, optochin-sensitive and soluble in bile were identified as S. pneumoniae. The isolates were serotyped by cmPCR. The database had been built with the statistical program SPSS (Chicago, IL, USA) version 18.0. The possible risk factors were assessed by multivariate Poisson regression. The level of probability of 0.05 (two-tailed) was used to determine statistical significance. The prevalence of pneumococcus carrier was 57.6% (CI95%: 54.2% - 60.9%). According to the multivariate Poisson regression analysis, children aged 36-47 months (IRR: 1.117; CI95%: 1.007-1.238; p: 0.035) and children in whose houses had four or more residents (IRR: 1.1214; CI95%: 1.078-1.368; p 0.001) were considered risk factors independently associated to pneumococcal colonization. The variable family income equal to or greater than three minimum wages was considered a protective factor independently associated to pneumococcal colonization (IRR: 0.787; CI95%: 0.627-0.990; p 0.041). The most prevalent serotypes and serogroups founded were 6A/6B/6C/6D (n=80; 16.3%), 14 (n=47; 9.6%), 23F (n=46; 9.4%), 19F (n=43; 8.8%), 15B/15C (n=30; 6.1%), 11A/11D (n=28; 5.7%), 3 (n=22; 4.5%) and 19A (n=16; 3.3%). Our results showed a high prevalence of pneumococcal colonization among the study population, indicating that colonization by this microrganism is common among children, especially in environments that favor crowding. The main serotypes/serogroups are cover by PCV10.